Analisis Kesalahan Mahasiswa Program Studi Pendidikan Matematika STKIP Hermon Timika dalam Menyelesaikan Soal Kalkulus Integral Berdasarkan Newman's Error Analysis dan Upaya Pemberian Scaffolding: Analisis Kesalahan Mahasiswa Program Studi Pendidikan Matematika STKIP Hermon Timika dalam Menyelesaikan Soal Kalkulus Integral Berdasarkan Newman's Error Analysis dan Upaya Pemberian Scaffolding - A. Rasul; Jhon Citro Trisakti (Mandalika Mathematics and Educations Journal, 2022)
Integral calculus is one of the mathematics courses that requires an adequate level of reasoning, communication skills and higher-order thinking skills to be able to understand and solve problems. The purpose of this study was to identify student errors based on Newman's Error Analysis (NEA) in solving integral calculus problems accompanied by the provision of scaffolding. The research subjects were students of STKIP Hermon Timika's Mathematics Education Study Program who attended integral calculus lectures. The results showed that there were no errors made by students on indicator type 1 (reading error), the average student made an error in indicator 2 (comprehension error) of 39%, the average error on indicator 3 (transformation error) was 71%. , the average error in indicator 4 (process skills error) is 76% and the average error most often made in indicator 5 (encoding error) is 87%. The scaffolding used to overcome all student errors only reached level 2 scaffolding, namely explaining, reviewing, and restructuring. The provision of scaffolding by lecturers is to explain, review and restructure so as to encourage students to correct these mistakes. Based on the results of this study, lecturers are expected to conduct meaningful lecture activities for students of STKIP Hermon Timika's Mathematics Education Study, so that it is not easy to forget the material concepts that have been explained.